IDENTIFIKASI JENIS TUMBUHAN ASING INVASIF DI HUTAN PENDIDIKAN TATANGGE TAMAN NASIONAL RAWA AOPA WATUMOHAI (TNRAW) - Made Sri Martini (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2021)
Tatangge Education Forest is part of the Rawa Aopa Watumohai National Park which includes a utilization zone that is used for scientific research purposes, to support culture, tourism and nature recreation. The study aims to determine the types of invasive alien species in the Tatangge Education Forest Rawa Aopa Watumohai National Park, which was carried out in the Tatangge Education Forest Rawa Aopa Watumohai National Park from August to September 2021 using the purposive sampling method. Based on the results of the study, obtaibed 24 types of invasive alien species spread ove the 3 largest ecosystem types in a row, namely in the savanna ecosystem found as many as 16 species, in the forest ecosystem as many a 15 species and swamp ecosystem found only 5 species.